Immunogenicity of the recombinant adenovirus fusion-expressing E0-E2 gene of the classical swine fever virus - Zhang, Heng; Yin, Dehua; Qin, Huairui; Zhang, Ke; Li, Zhaoyang; Cui, Guangchao; Ma, Guangbin; Sun, Peng; Cao, Zhi (Frontiers in Microbiology, 2022)
Adenovirus vector vaccines have been the mainstream research direction of CSF vaccines, due to the replication deficiency of adenovirus vector, making it achieve double effects with safety of inactivated vaccines and efficacy of live vaccines. Therefore, E0 and E2 gene were expressed by adenovirus vector and recombinant adenovirus E0-E2 (rAd-E0-E2) vaccine was constructed, and the minimum immunization dose and immune duration preiod were determined in this study. 40 healthy piglets were randomly divided into 8 groups (n = 5). Groups 1 ~ 5 were used to determine the minimum immunization dose, and 5 groups were inoculated with rAd-E0-E2 with different immune dose. Serum was collected at 7 d and 14 d after immunization to detect CSFV antibodies by ELISA, and piglets were challenged at 7 d post immunization. The groups 6 ~ 8 were immunized with 1 dose of the rAd-E0-E2, the CSFV C strain and saline, respectively to identify the immune duration period. Serum was collected at different time points after immunization and CSFV antibodies were detected by ELISA, and piglets were challenged at 8 months post immunization; Meanwhile, temperature, clinical symptoms and pathology were observed. The results of 1 ~ 5 groups showed that 1 piglet was protected after challenge, and 4 piglets exhibited high fever retention, typical CSFV symptoms and tissue lesions in 1/50 dose group, whereas no clinical symptoms were observed in the 1/10 dose, 1/5 dose and 1 dose groups with 5/5 protection after challenge. And the minimum dose was determined as 1/10 dose. The results of 6 ~ 8 groups showed that all piglets were survived after challenge, but the antibody level of rAd-E0-E2 strain was higher than that of C strain at 8 months post immunization, and all piglets in the negative group developed disease process after challenge. Above all, the minimum immunization dose of rAd-E0-E2 was 1/10 dose (3.16×106.0 IFU) and the minimum immune dose was determined as 1 dose (3.16×107.0 IFU) to achieve expected effects. The immune duration period of piglets immunized with 1 does of rAd-E0-E2 was at least 8 months.